Study on the dissolution of intermetallic compounds and austenite grain growth behavior in Cr-Ni-Mo-Ti-Al ultra-high strength stainless steel - Jiahao Chen; Zhenbao Liu; Xiaohui Wang; Fengchun Jiang; Yuqiao Zhang; Zhiyong Yang; Jianxiong Liang; Wenyu Zhao (Materials Research Express)
In this work, the austenite grain growth behavior of an ultra-low carbon cobalt-free ultra-high strength stainless steel is studied in the temperature range of 820 °C–1020 °C and the holding time of 0–150 min. The experimental results indicate that in the temperature range below 880 °C, there are a large number of Fe _2 Mo-type Laves phases in the steel. The austenite grain size shows no significant change (∼23 μm) upon increasing the isothermal holding temperature or extending the holding time below 880 °C, which is attributed to the pinning effect of the Laves phases. At holding temperatures of 900 °C–960 °C, partial dissolution of the Laves phases reduces their pinning efficacy, triggering incipient grain growth. When the temperature is further increased to 980 °C or above, the Laves phase completely dissolves during the initial heating stage. The grains undergo accelerated coarsening with increasing isothermal holding temperature and prolonged holding time. Mathematical models for austenite grain growth in ultra-low-carbon cobalt-free ultra-high strength stainless steel are established in the temperature ranges of 900 °C–960 °C and 980 °C–1020 °C, with the optimal grain growth exponents (n) determined as 1.518175 and 1.614925, respectively. This study clarifies the effects of heating temperature, holding time, and initial grain size on austenite grain growth. The accuracy and reliability of the model are validated by comparing calculated values with experimentally measured data, achieving an average absolute relative error (AARE) of 1.33026% and a coefficient of determination (R ^2 ) of 0.99768.